Integrated analyses of SNP-genotype and environmental data in a continuously distributed snapper species (Lutjanus johnii, Bloch, 1792) reveals a mosaic of populations and a challenge for sustainable management. (1st October 2021) - Taillebois, Laura; Davenport, Danielle; Barton, Diane P; Crook, David A; Saunders, Thor; Hearnden, Mark; Saunders, Richard J; Newman, Stephen J; Travers, Michael J; Dudgeon, Christine L; Maher, Safia L; Ovenden, Jennifer R
Abstract: Understanding population structure is important for predicting the outcomes of anthropogenic development, harvest, and environmental change on the abundance of fisheries species. Logically, the use of several data sources is best for delineating population structure, but combining across data types adds extra challenges as results can be incongruent. Here, genetic and environmental markers were used to test hypotheses about population structure in a collection of 523 tropical inshore finfish ( Lutjanus johnii ) across northern Australia from 20 locations. Redundancy analyses (RDA) were used to statistically test for correlations among data sources providing a basis for reconciliation and insights into ecological and evolutionary processes. Genomic data (10349 SNP loci) revealed low, but significant genetic divergence (max FST 0.0402) between 16 locations. A total of 12 putative contiguous biological stocks were proposed whose distributions were correlated with IMCRA bioregions but not to existing regions used for management of the fishery. RDA showed a significant correlation between environmental markers (otolith chemistry and parasite abundances) and SNP genotype in two of three region-wide analyses supporting the proposed stock structure, and suggesting that L. johnii may be locally adapted to the heterogeneous environment. These findings are significant for the conservation of the commercially and recreationally important L. johnii and can be used to guide future fisheries management actions.